Behavior of portable fiber reinforced concrete vehicle barriers subject to blasts from contact charges - Coughlin, A.M.; Musselman, E.S.; Schokker, A.J.; Linzell, D.G. (International journal of impact engineering, 2010)
Portable concrete barriers are commonly used to form a secure perimeter to prevent entry of terrorist vehicle borne improvised explosive devices (VBIEDs). Barrier effectiveness can be compromised when satchel charges are used to breach a protective perimeter and subsequently permit closer access to the intended target by VBIEDs. The behavior of five portable concrete vehicle barriers was tested under satchel sized contact charge explosives at the Air Force Research Labs (AFRL) test range at Tyndall Air Force Base, Florida. Four barriers representing different fiber reinforced concretes (FRCs) including two types of synthetic FRC, two steel-synthetic blend FRCs with different fiber volumes, and a traditional reinforced normal weight concrete which served as the control specimen. Each of the FRCs exhibited less material loss and surface damage compared to the control. The two steel synthetic blended concretes exhibited the least amount of damage of all barriers, with no visible difference in performance between the two fiber volumes. The control barrier had widespread spalling and limited concrete in the core of the specimen remained intact. A finite element model was created in LS-DYNA to model one FRC barrier and the control barrier to see if the models could predict the observed damage. Both models were deemed successful due to their ability to show similar patterns of damage as the tested barriers.